Gene effects and combining ability for head diameter in sunflower inbred lines - Joksimović Jovan; Atlagić Jovanka; Škorić Dragan (Selekcija i Semenarstvo, 2000)
The object of the study were 8 divergent sunflower inbred lines and 15 F, hybrids, which were analyzed for mode of inheritance, gene effects, combining ability and the components of genetic variance. Combining ability determinations were made by the method line x tester (Singh and Chouduary, 1976). Regarding the inheritance of head diameter, super dominance (positive heterosis) occurred in 10 hybrid combinations, dominance of the better parent in 5. Non-additive gene action predominated in the control of the examined characteristic. The inbred lines HA-BCPL and RHA-178 had highly significant positive values of general combining ability (GCA) for head diameter. The inbreeds HA-74 and RHA-N-K had highly significant negative GCA values. The hybrid combination HA-BCPL x RHA-178 had highly significant values of specific combining ability (SCA) for the characteristic under study The inbreeds HA-BCPL and RHA-178 were distinguished on the basis of their GCA and SCA values as usable in the development of sunflower hybrids. The obtained GCA/SCA ratio (0.595) confirmed the prevalence of non-additive gene action in the control of head diameter.